The spectrum of non-characteristic oral manifestations in COVID-19 - a scoping brief commentary - Hanna Hüpsch-Marzec; Arkadiusz Dziedzic; Dariusz Skaba; Marta Tanasiewicz (Nofer Institute of Occupational Medicine, 2021)
Virus-induced oral abnormalities, occurring especially in severe COVID-19 cases of hospitalized patients, have various characteristics and clinical features being, either directly or indirectly, related to SARS-CoV-2 infection. Deregulation of the immune system as a result of SARS-CoV-2 infection may lead to the impairment of the normal defense pathway in the SARS-CoV-2 positive patients. This scoping mini-review is aimed to critically appraise the existing evidence concerning the potential link between COVID-19 condition and abnormal manifestations within oral cavity, affecting oral mucosa, salivary glands and sensory elements. COVID-induced oral mucosa manifestations, with various clinical aspects, are likely to occur as coinfections and secondary symptoms, as immune system imbalance is per se a causative factor of secondary manifestations. Oral mucosal lesions related to SARS-CoV-2 infection do not seem to demonstrate gender predilection, with the average reported age around 50 years of age. They include mainly white and erythematous plaques, ulcers, blisters, petechiae. The affected intraoral areas were mainly: tongue, palate, lips, gingiva, and buccal mucosa. The "aggressive" therapies utilized to treat COVID-19, including drug interactions may aggravate or initiate OMLs pathologies. Neglected oral hygiene or partial or complete abandonment of oral hygiene during intensive hospitalization constitutes an independent factor promoting a wide range of oral pathologies. In addition, stress factor indirectly impairs functioning of the immune system. Oral mucosa lesions occurring in COVID-19 cases present with a wide variation of non-characteristic features. These intraoral, soft tissues abnormalities seem to be reversible and transient. A potential impact of severe oral pathologies to systemic health resulting from SARS-CoV-2 infection, along with associated poor oral hygiene should not be ignored, predominantly in seriously ill patients hospitalized in intensive care units. Med Pr. 2021;72(6):685-92